Mediated audits - Martin Pollrich (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
I study the optimal audit mechanism when the principal cannot commit to an audit strategy. Invoking a relevation principle, the agent reports her type to a mediator whi assigns contracts and recommends the principla whether to audit. For each reported type the mediator randomizes over a base-contract and the audit contract, accompanied by a recommendation to audit. For large penalties the optimal mechanism uses strictly more contracts than types and cannot be implemented via offering a menu of contracts. The analysis provides a proper benchmark for studying auditing under limited commitment and sheds new light on the usefulness of mediation in contracting and on the design of optimal mechanisms.
Keywords: D82; D86; C72; 330; auditing; limited commitment; mediation; contract theory